A dictionary of stylistics - Katie Wales (Cambridge Univ. Press, 1990)
The book is a major reference work of the terminology used in stylistics together with its related disciplines of discourse analysis, text linguistics, literary theory and literary criticism. It contains over 600 alphabetically-listed entries drawing widely on areas such as sociolinguistics, semiotics, grammar, communication theory, poetics and traditional rhetoric